Femtosecond laser-assisted deep anterior lamellar keratoplasty in phototherapeutic keratectomy versus the big-bubble technique in keratoconus - Jarbas Pereira de Macedo (International Journal of Ophthalmology, 2018)
AIM: To compare the functional and anatomic results of femtosecond laser (FSL)-assisted deep anterior lamellar keratoplasty (DALK) associated with phototherapeutic keratectomy (PTK) and FSL-assisted DALK performed using the big-bubble technique in keratoconus. METHODS: During the first phase of the study, an electron microscopy histopathology pilot study was conducted that included four unsuitable donor corneas divided into two groups: in FSL group, FSL lamellar cuts were performed on two corneas and in FSL+PTK group, PTK was performed at the stromal beds of two corneas after FSL lamellar cuts were made. During the second phase of the study, a randomized clinical trial was conducted that included two treatment groups of patients with keratoconus: group 1 (n=14 eyes) underwent FSL-assisted DALK associated with PTK and group 2 (n=12 eyes) underwent FSL-assisted DALK associated with the big-bubble technique. The main outcome measures were the postoperative visual acuity (VA) and optical coherence tomography (OCT) measurements, confocal microscopic findings, and contrast sensitivity. RESULTS: In the pilot study, histopathology showed a more regular stromal bed in the FSL+PTK group. In the clinical trial, group 1 had significantly worse best spectacle-corrected VA and contrast sensitivity (P<0.05 for both comparisons). The residual stromal bed measured by OCT was significantly (P<0.05) thicker in group 1. Confocal microscopy detected opacities only at the donor-receptor interface in group 1. CONCLUSION: Patients with keratoconus treated with FSL-assisted DALK performed using the big-bubble technique fare better than treated with FSL-assisted DALK associated with PTK.